Chromosomal microarray analysis for the detection of chromosome abnormalities in fetuses with echogenic intracardiac focus in women without high-risk factors - He, Min (Medicine (Baltimore), 2020)
To investigate the association between pathogenic copy number variants (p-CNVs) and abnormal karyotypes detected by chromosomal microarray analysis (CMA) and echogenic intracardiac focus (EIF). This was a retrospective study of fetuses with EIF with CMA data at the Prenatal Diagnosis Center of the West China Second University Hospital of Sichuan University between September 2014 and May 2017. Fetuses were assigned to the isolated EIF and non-isolated EIF groups according to the presence of other ultrasound abnormalities. Among 244 pregnant women, there were 143 cases of isolated EIF and 101 of non-isolated EIF. CMA revealed chromosome abnormality (n = 9 (3.7%): trisomy 21, n = 4; sexual trisomy, n = 2; and p-CNV, n = 3), variants of unknown significance (VOUS, n = 19), and benign CNV (b-CNV, n = 216). Among the fetuses with isolated EIF, 5 had chromosomal abnormalities (3.5%). Among the fetuses with non-isolated EIF, four had chromosomal abnormalities (4.0%). All fetuses with trisomy 21 were in the non-isolated group. The frequency of labor induction was 66.7% (6/9) among the fetuses with chromosome abnormality and 21.1% (4/19) among those with VOUS. Among those with chromosomal abnormalities, one (11.1%) had congenital heart disease. In pregnant women without high-risk factors for chromosomal abnormalities, ultrasound abnormalities, including EIF, could be an indication for CMA. Ultrasound abnormalities (including EIF) and chromosome abnormality could indicate a high risk of CHD. The presence of EIF and at least another ultrasound abnormality could indicate a high risk of trisomy 21.